Measuring the Dash - Lynne S. Wilcox, MD, MPH (Centers for Disease Control and Prevention, 2005)
Individuals in the United States paradoxically long for and dread old age. The alternative to growing old is an outcome few of us would prefer. But aging seems inevitably associated with decline. Independent choices, a hallmark of adulthood, can be lost between one day and the next with a heart attack, a stroke, or a fractured hip. Senior citizen discounts notwithstanding, our culture does not offer a valued place for elders. It becomes easy to focus on what we will certainly lose rather than on any uncertain gains associated with aging. And yet, we have examples of thriving elders. Former President Jimmy Carter won the Nobel Peace Prize in 2002 at age 78. Dr Benjamin Mays, a president of Morehouse College and mentor to Martin Luther King, Jr, and Andrew Young, published his autobiography Born to Rebel at 76. Celia Cruz, the Cuban American singer called the "Queen of Salsa," whose songs earned 22 gold records, continued performing and recording until her death at 78.